If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 11 = 7x + 5 Reorder the terms: 11 + 4x = 7x + 5 Reorder the terms: 11 + 4x = 5 + 7x Solving 11 + 4x = 5 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 11 + 4x + -7x = 5 + 7x + -7x Combine like terms: 4x + -7x = -3x 11 + -3x = 5 + 7x + -7x Combine like terms: 7x + -7x = 0 11 + -3x = 5 + 0 11 + -3x = 5 Add '-11' to each side of the equation. 11 + -11 + -3x = 5 + -11 Combine like terms: 11 + -11 = 0 0 + -3x = 5 + -11 -3x = 5 + -11 Combine like terms: 5 + -11 = -6 -3x = -6 Divide each side by '-3'. x = 2 Simplifying x = 2
| 2x+9=7x+3 | | 3/4x8x | | (4a+8x)(7a-5x)= | | -1(x-y)+3(y-x)= | | (2w+2b)(3w+5b)= | | (ln(4)^2/(2ln2)-(ln(2)^2)/(2ln2) | | 30=3x-9 | | 2lnx-6=0 | | -5=0.25(4t+20r)-8r | | 1-4x/2x-1 | | 8sinx+16=20 | | t(2+-5t+3t^2)=0 | | 8+3x=x | | n^2+4n+16=0 | | 15z-(-3x-10x)= | | 2x^2+28=1 | | 3x-5y=42 | | n^3-64=0 | | X-0.6x=12 | | h^2+6h+9= | | 3x^2-60x+400=0 | | 7a+4b=32 | | 3(2x-4y)-2(2x-5y)+2y= | | ln(4x+5)=ln(2x-1)+ln(3) | | x+(x+1)+(x+2)+(x+3)=66 | | 2x+96-0= | | 4y+3=14 | | 38x+5y= | | 4y+4x-xy=0 | | 2p^2-2p/7p-7= | | Sqrt[x]=30 | | x-4y-12=0 |